2014
DOI: 10.3415/vcot-13-04-0046
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of normal joint angles by goniometry in calves

Abstract: The data of this study acquired objective and useful information on the normal forelimb and hindlimb joint angles in normal Holstein calves. Further studies can be done to predict detailed goniometric values from different diseases and compare them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…For the first time, the fetlock joint angle in calves with contracted flexors has been recorded. The goniometric measurements of limb joints only proximal to the fetlock joints in healthy, awake Holstein Friesian calves restrained in lateral recumbency (Sirin et al 2014) and standing sheep (Govoni et al 2012) were recently reported. In the calves of the present study, the angle of the fetlock deflection varied from 30° to 65°.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the first time, the fetlock joint angle in calves with contracted flexors has been recorded. The goniometric measurements of limb joints only proximal to the fetlock joints in healthy, awake Holstein Friesian calves restrained in lateral recumbency (Sirin et al 2014) and standing sheep (Govoni et al 2012) were recently reported. In the calves of the present study, the angle of the fetlock deflection varied from 30° to 65°.…”
Section: Discussionmentioning
confidence: 99%
“…The foot of the limb placed on the upper side was extended slightly and, using a protractor, the angle formed between a central longitudinal arbitrary line on the lateral aspect of the metacarpal or metatarsal bone with that of the central line of the corresponding foot was recorded (Sirin et al 2014). The calves were then restrained on the contralateral side and the fetlock angle recorded in the same manner.…”
Section: Introductionmentioning
confidence: 99%
“…The angle of the knuckling was measured following the procedure described by Sirin et al [ 13 ] with minor modifications. Briefly, the calves were confined without any prior medication in lateral recumbency.…”
Section: Methodsmentioning
confidence: 99%